A STUDY OF SPEECH ACTS PRODUCED BY THE MAIN CHARACTER IN DORAEMON COMIC THE 1 st VOLUME - MARDIANTI, IIS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: Communication, Doraemon Comic the 1st Volume, Pragmatics,Locutionary Acts, Illocutionary Acts and Types of Sentences. Communication occurs because there is a connection between the speaker and the listener. This study deals with the intended meaning of the speaker that is called pragmatics. In pragmatics the study related to the meaning called speech acts because speech acts covers people’s problem to understand the meaning behind the utterance. There are three different levels of speech acts however the writer focus on analyzing the utterance that contain locutionary acts and illocutionary acts in Doraemon comic the 1st volume because connected with the intended meaning that do not realize by the reader when they read the comic. There are two problems of this study: (1) What are the types of locutionary acts produced by the main character in Doraemon Comic the 1st Volume? (2) What are the types of illocutionary acts produced by the main character?. This study is a qualitative research analysing the data that are related to the text of Doraemon Comic the 1st Volume. The writer analyzed the utterances that contain locutionary and illocutionary acts based on Searle’s theory (1976). The writer limited the data collection only chapters 1-4 of the comic because the data have been saturated which means the utterances show the same characteristic. Based on the result, there are 48 utterances containing speech acts from chapter one to chapter four (All the Way from a Future World, Prognosis of Doraemon, Transforming Biscuit and Spy Set). The writer found 17 utterances containing illocutionary acts in form of representative, 8 utterances containing commisive, 21 utterances containing directive and 2 utterances containing expressive. In addition, the writer also found 29 declarative sentences used to express gratitude, statement and advice, 7 imperative sentences to express order or request, and 12 interrogative sentences to express question. Meanwhile, the writer does not find the types of illocutionary acts containing declaration. In this study, the most frequent types of illocutionary acts is directives because the speaker wants the listener to do some actions intended by the speaker. In addition, the writer would like to give some suggestions for the future researchers that they use the newest theory to improve their studies. In addition, the writer hopes that the future researchers can use other media, such as: novels, movies, newspapers or advertisements.